WAYS TO IMPROVE THE EFFICIENT FORMATION AND MANAGEMENT OF INVESTMENT RESOURCES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the fundamental principles and practical strategies for improving the formation and management of investment resources, particularly in emerging economies. Efficient investment resource mobilization and allocation are critical for accelerating economic growth, enhancing infrastructure development, and ensuring long-term financial stability. The study evaluates the current structure of investment sources—including public funds, foreign direct investments, and corporate savings—and identifies major challenges such as inefficiency, lack of transparency, and weak regulatory environments. Drawing on international best practices, the paper proposes policy recommendations aimed at enhancing digital oversight, strategic planning, and public-private cooperation. Data tables and graphical analysis provide visual insights into investment trends and performance comparisons across selected countries. The findings emphasize the urgent need for systemic reforms to optimize investment effectiveness in alignment with national development priorities.